"If God hadn't invented woman men would have had to do so" - construction of female identities in Parade's End by Ford Madox Ford - Palin, Sara (My University, 2016)
The subject of the thesis is Parade's End (1924–1928) by Ford Madox Ford. The thesis focuses on the portrayal of female identities and femininity in the context of societal changes in the beginning of 1900s and also uses two of Ford's essays about gender and women's rights as background. The construction of female identities is discussed via different themes. The themes are marriage, divorce and infidelity; motherhood, modernity and emergence of new gender identities in post-World War I environment, and polyamory as a solution for adulterous practices and empty, unhappy marriages. Parade's End portrays superficially modern female identities, but ends up enforcing women's role as mother and traditional femininity. However, the novel suggests that the strict gender boundaries are starting to fracture after WWI. This is depicted by portraying the men representing new masculinity as feminised and emphasising androgyny and boyishness when discussing representations of new femininity.